2020
DOI: 10.2147/copd.s267002
|View full text |Cite
|
Sign up to set email alerts
|

<p>Defining Chronic Mucus Hypersecretion Using the CAT in the SPIROMICS Cohort</p>

Abstract: Background: Chronic cough and phlegm are frequently reported chronic obstructive pulmonary disease (COPD) symptoms. Prior research classified chronic mucus hypersecretion (CMH) based on the presence of these symptoms for ≥3 months, called chronic bronchitis (CB) if respiratory infection symptoms were present for 1-2 years (Medical Research Council [MRC] definition). We explored whether the COPD Assessment Test (CAT), a simple measure developed for routine clinical use, captures CMH populations and outcomes sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 26 publications
(37 reference statements)
4
23
1
Order By: Relevance
“…In a previous study, we showed that patients with CAT score-de ned CB shared clinical characteristics and outcomes with patients who had classically de ned CB [15]. While cut-off values have not been validated in other populations, a recent study based on Subpopulations and Intermediate Outcomes Measures in COPD Study (SPIROMICS) data suggested CAT1 and CAT2 cut-off scores of ≥ 2 [17]. Further studies are needed to validate a CAT score-based de nition of CB in other populations.…”
Section: Discussionmentioning
confidence: 96%
“…In a previous study, we showed that patients with CAT score-de ned CB shared clinical characteristics and outcomes with patients who had classically de ned CB [15]. While cut-off values have not been validated in other populations, a recent study based on Subpopulations and Intermediate Outcomes Measures in COPD Study (SPIROMICS) data suggested CAT1 and CAT2 cut-off scores of ≥ 2 [17]. Further studies are needed to validate a CAT score-based de nition of CB in other populations.…”
Section: Discussionmentioning
confidence: 96%
“…The clinical significance of the CB phenotype in COPD is well-established. CB is associated with poor health-related quality of life [ 22 25 ], poor functional exercise capacity [ 26 ], low lung function [ 11 , 22 , 23 , 27 , 28 ], more frequent exacerbations [ 11 , 17 , 22 , 23 , 27 ], and higher mortality [ 24 , 29 ]. Consistent with those previous findings, our study showed higher mMRC and CAT scores, worse 6MWT performance, worse lung function, and more frequent exacerbations in CB patients than in non-CB patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, there may be recall bias during long-term evaluations and the definitions of CB are complicated; thus, other parameters have been used in some studies, including chronic cough, physician diagnosis, and the presence of cough and sputum for 3 months over > 1 year [ 12 , 13 , 36 ]. Symptom-based scores (e.g., SGRQ and CAT) have also been employed [ 11 , 15 , 17 , 21 , 27 ]. Such scoring systems allow symptom severity to be quantified based on cut-off values, rather than subjective definitions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations